2021
DOI: 10.1039/d1tc04180k
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in humidity sensors for human body related humidity detection

Abstract: For a long time, humidity sensors have been mainly used in detecting humidity of ambient conditions, such as, industry, agriculture, and smart home. With the development of wearable electronic systems,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
117
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(120 citation statements)
references
References 143 publications
3
117
0
Order By: Relevance
“…Various materials, such as two-dimensional (2D) materials [11,12], polyelectrolytes [13] and metal oxides [14], have been researched. Among them, 2D GO materials have attracted much attention because of their many features, such as a high specific surface area, a high mechanical modulus, easy stacking, easy functionalization and luxuriant oxygen-containing functional groups [15][16][17][18]. However, previous studies [19] found that the interlayer spacing of GOMs is 12.8 ± 0.2 Å, even when completely immersed in water.…”
Section: Introductionmentioning
confidence: 99%
“…Various materials, such as two-dimensional (2D) materials [11,12], polyelectrolytes [13] and metal oxides [14], have been researched. Among them, 2D GO materials have attracted much attention because of their many features, such as a high specific surface area, a high mechanical modulus, easy stacking, easy functionalization and luxuriant oxygen-containing functional groups [15][16][17][18]. However, previous studies [19] found that the interlayer spacing of GOMs is 12.8 ± 0.2 Å, even when completely immersed in water.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to monitoring human respiration, fast-response humidity sensors can be used to monitor human physiological behaviors, as shown in this section [ 164 ]. Duan et al summarized recent advancements in humidity sensors for human-body-related observations [ 17 ]. The recognition of verbal words has been reported from breath air [ 54 , 104 , 111 , 135 , 165 ].…”
Section: Other Application For Physiological Monitoringmentioning
confidence: 99%
“…Humidity is also a valuable observable for contact-based health monitoring. Humidity sensors with ultrafast response and recovery times have been recently proposed in the field of materials science [ 16 , 17 ]. Functional nanomaterials play an important role in speeding up the response and recovery rates of the sensors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is necessary to summarize the research results emerged in the past decade to follow the rapid development of hierarchical metal oxide-based sensing materials, and find the rules to design and synthesize metal oxides with higher sensing performance. In addition, several excellent reviews on gas sensing mechanism, [32] the detection of various gases, [33][34][35] the sensing materials with different dimensions, [36][37][38] gas sensors based on heterojunction, [39,40] semiconductors metal oxides based gas sensors, [41][42][43] and the applications of gas sensors [44][45][46] may further help to understand the present state of metal oxide-based gas sensors from different perspective. However, few of them focus on the diversity of the application environment of the gas sensors.…”
mentioning
confidence: 99%